Indicadores de sostenibilidad de la actividad turística de la provincia de San Martin - Panduro Villacorta, Liseña (2006)
The present titled thesis "lndicating of Sustainability of the Tourist Activity of the Province of San Martín" leaves from the problem. Which is the relation that settles down between the indicators of sustainability and the tourist activity of the Province of San Martin? lt must like intention determine the indicators of sustainability of the tourist activity of the Province of San Martín, that serve to evaluate the impact on the existing biodiversity and to plan their sustainable development. The used methodology corresponds to the design of descriptive type - comparative that relates the implication between the raised variables. From this process the presentation of the data as well as its analysis and interpretation are derived to get to propose a set of indicators to start off of tour subsystems: Environmental and use of the territory, economic, sociocultural and of partícipation and management. to which the lists of credits of the indicators proposed to being used for the exposition correspond, direction, pursuit, monitoreo and control, for the sustainable tourist development of the province of San Martín.